2017
DOI: 10.1093/biolinnean/blw016
|View full text |Cite
|
Sign up to set email alerts
|

Adult human perception of distress in the cries of bonobo, chimpanzee, and human infants

Abstract: 19Understanding the extent to which humans perceive the emotional state of animals has both 20 theoretical and practical implications. While recent studies indicate that natural selection has 21 led to some convergence of emotion coding among vertebrate species (including humans), 22highlighting the interspecific value of emotional signals, it has also been argued that 23 interspecific communication of emotions can fail due to species-specific signaling traits 24 impairing information decoding, and/or absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 48 publications
11
41
0
Order By: Relevance
“…This interpretation is strongly supported by the inclusion of acoustic Mahalanobis distance for each species compared to humans as covariate of interest. Additionally, previous research showed a higher pitch in young bonobo screams in comparison to chimpanzee and human baby cries 38 , giving steam to the crucial role of acoustic Mahalanobis distance in our results. Therefore, it seems reasonable to hypothesize that TVA activity is not human-specific 2,6 per se but that it would instead be sensitive to the vocalizations of other primate species, provided that such vocalizations share sufficient acoustic (and phylogenetic) proximity with the human vocal signal.…”
Section: Discussionsupporting
confidence: 77%
“…This interpretation is strongly supported by the inclusion of acoustic Mahalanobis distance for each species compared to humans as covariate of interest. Additionally, previous research showed a higher pitch in young bonobo screams in comparison to chimpanzee and human baby cries 38 , giving steam to the crucial role of acoustic Mahalanobis distance in our results. Therefore, it seems reasonable to hypothesize that TVA activity is not human-specific 2,6 per se but that it would instead be sensitive to the vocalizations of other primate species, provided that such vocalizations share sufficient acoustic (and phylogenetic) proximity with the human vocal signal.…”
Section: Discussionsupporting
confidence: 77%
“…Whether this interspecific dimension is innate or acquired through learning remains an open question. It is indeed well established that acoustic signals coding for emotional states share similar acoustic features across mammalian species [33]: although interspecific communication may suffer from limitations [34][35][36], emotion-dependent similarities may derive from shared, ancestral production constraints or reflect convergent evolution in response to common selection pressures [37]. Dogs and wolves emit highpitched tonal vocalizations in greeting contexts, between adults or between cubs, and as a solicitation for food or care [38], and it is likely that puppies are innately receptive to any high-pitched signals with a pronounced harmonicity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that calls are sufficiently close acoustically to be accepted as functionally equivalent and elicit the same behaviour 3 , 24 . However, a study investigating the spontaneous ability of naïve human adults to assess the emotional content of vocalizations in closely related ape species, including bonobos ( Pan paniscus ) and chimpanzees ( P. troglodytes ), showed that listeners responses were strongly biased by basic frequency differences 25 , indicating that in the absence of exposure and/or training, the interspecific relevance of emotional signals can be limited by simple acoustic scaling differences 25 .…”
Section: Introductionmentioning
confidence: 99%